2017
DOI: 10.1111/jir.12358
|View full text |Cite
|
Sign up to set email alerts
|

Where is the ‘subjective straight ahead’ in Williams syndrome?

Abstract: Individuals with WS showed a significant leftward deviation in the SSA task. This bias of the body's longitudinal axe representation could have a negative impact on the use of an egocentric reference system, which could be the cause for their difficulties in defining spatial relations (e.g. location and orientation) necessary for performing spatial tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…This bias is more pronounced in the right space as observed among neglect patients after a stroke in right hemisphere, independently of handedness. Results showed a left bias in the WS group, which is consistent with the deviation of the body representation found in the WS population (Saj & al., ). These authors reported that the WS population presents a leftward deviation on the SSA task.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This bias is more pronounced in the right space as observed among neglect patients after a stroke in right hemisphere, independently of handedness. Results showed a left bias in the WS group, which is consistent with the deviation of the body representation found in the WS population (Saj & al., ). These authors reported that the WS population presents a leftward deviation on the SSA task.…”
Section: Discussionmentioning
confidence: 97%
“…Individuals with Williams syndrome (WS) have shown to present a deviation of body representation (Saj, Heiz & Barisnikov, ) as they exhibited a significant left deviation on the subjective straight‐ahead (SSA) compared with the chronological age (CA) control group and a marginal left deviation compared with the young children control group. The results for the latter group could be related to the progressive maturation of the neuronal network (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A low recognition of and naming of body parts and difficulties in identifying the right and the left parts of own or other bodies has also been reported (Heiz, Cengic, Fernandes, & Barisnikov, 2015). According to a recent study (Saj, Heiz, & Barisnikov, 2017), these body representation difficulties in WS participants may be explained by a significant left deviation of their bodily sagittal plan, which allows an individual to determine a spatial location (e.g., on my left/right). The lack of a well-established representation of left and right directions might, according to Bernardino and colleagues (2013), introduce additional difficulties for WS participants.…”
Section: Discussionmentioning
confidence: 99%